Influence of the Chemical Structure on Odor Qualities and Odor Thresholds of Halogenated Guaiacol-Derived Odorants - Juhlke, Florian; Lorber, Katja; Wagenstaller, Maria; Buettner, Andrea (Frontiers in Chemistry, 2017)
Chlorinated guaiacol derivatives are found in waste water of pulp mills using chlorine in the bleaching process of wood pulp. They can also be detected in fish tissue, possibly causing off-odors. To date, there is no systematic investigation on the odor properties of halogenated guaiacol derivatives. To close this gap, odor thresholds in air and odor qualities of 14 compounds were determined by gas chromatography-olfactometry. Overall, the investigated compounds elicited smells that are characteristic for guaiacol, namely smoky, sweet, vanilla-like, but also medicinal and plaster-like. Their odor thresholds in air were, however, very low, ranging from 0.00072 to 23 ng/Lair. The lowest thresholds were found for 5-chloro- and 5-bromoguaiacol, followed by 4,5-dichloro- and 6-chloroguaiacol. Moreover, some inter-individual differences in odor threshold values could be observed, with the highest variations having been recorded for the individual values of 5-iodo- and 4-bromoguaiacol.